1992
DOI: 10.1002/bit.260390308
|View full text |Cite
|
Sign up to set email alerts
|

Development of the optimal inoculation conditions for microcarrier cultures

Abstract: The environmental conditions under which anchorage-dependent mammalian cells are grown are not necessarily those under which a culture should be initiated. Cell attachment is a physical process, and those factors which affect forces involved in cell attachment differ from the biological factors which affect cell growth. We have conducted an extensive experimental study to define clearly the optimal environmental conditions for MRC-5 cell attachment onto microcarriers. These inoculation conditions are particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
1
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 16 publications
3
64
1
2
Order By: Relevance
“…Effects of culture conditions on Vero cell propagation on Cytodex 1 microcarriers Since various factors affect mammalian cell growth on microcarriers (Sun et al, 2000;Murkhopadhyay et al, 1993;Amersham Pharmacia Biotech, 1999;Forestell et al, 1992;Ng et al, 1996), a fractional factorial experimental design was carried out to help identifying the most appropriate conditions for obtaining high cell densities on Cytodex 1 microcarriers. The experimental conditions tested (expressed as normalized values), as well as the maximum cell densities obtained in the different runs, are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Effects of culture conditions on Vero cell propagation on Cytodex 1 microcarriers Since various factors affect mammalian cell growth on microcarriers (Sun et al, 2000;Murkhopadhyay et al, 1993;Amersham Pharmacia Biotech, 1999;Forestell et al, 1992;Ng et al, 1996), a fractional factorial experimental design was carried out to help identifying the most appropriate conditions for obtaining high cell densities on Cytodex 1 microcarriers. The experimental conditions tested (expressed as normalized values), as well as the maximum cell densities obtained in the different runs, are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…One of them is the ratio of inoculated cells to microcarriers. According to Forestell et al (1992), although inoculum density does not interfere with environmental conditions controlling cell adhesion, the cell-to-carrier ratio is an important parameter since it influences the distribution of cells on the spheres and determines the proportion of microcarriers that do not become occupied with cells (Ng et al, 1996). According to literature (Amersham Pharmacia Biotech, 1999), the key to obtain high cell yields in microcarrier cell cultures is to assure that all or almost all microcarriers are inoculated with cells, since bead-to-bead transfer does not frequently occur along cultivation.…”
Section: Introductionmentioning
confidence: 99%
“…Loss of cells during the inoculation procedure is a serious problem when limited quantities of cells are available. Forestell et al (1992) showed that optimal inoculation conditions can greatly improve the maximum cell density when culturing mammalian MRC-5 cells in bioreactors on microcarriers. When culturing hematopoietic stem cells, inoculation density has been shown to interact with other variables and greatly influence the culture performance (Koller et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in the case of adherent cell line cultures, a surface area as large as possible must be provided by the system so that the culture can achieve high cell densities. In addition, the best environment possible is required to allow the cells to exert their physiological functions in an optimized way and, consequently, to support virus replication to high titers (Croughan et al, 1987;Forestell et al, 1992;Hu et al, 1985a;Hu and Aunins, 1997;Kilburn, 1991;Pharmacia, 1981;van Wezel, 1967van Wezel, , 1982.…”
Section: Introductionmentioning
confidence: 99%